PM2.5 Airborne Particulates Near Frac Sand Operations - Walters, Kristin; Jacobson, Jeron; Pierce, Crispin; Kroening, Zachary (Journal of Environmental Health, 2015)
The rapid growth of hydraulic fracturing for oil and gas extraction in the U.S. has led to 135 active "frac" sand mines, processing plants, and rail transfer stations in Wisconsin. Potential environmental health risks include increased truck traffic, noise, ecosystem loss, and groundwater, light, and air pollution. Emitted air contaminants include fine particulate matter (PM2.5) and respirable crystalline silica. Inhalation of fine dust particles causes increased mortality, cardiovascular disease, lung disease, and lung cancer. In the authors' pilot study, use of a filter-based ambient particulate monitor found PM2.5 levels of 5.82-50.8 pg/m3 in six 24-hour samples around frac sand mines and processing sites. Enforcement of the existing U.S. Environmental Protection Agency annual PM2.5 standard of 12 pg/m3 is likely to protect the public from silica exposure risks as well. PM2.5 monitoring around frac sand sites is needed to ensure regulatory compliance, inform nearby communities, and protect public health. Posted with permission from the Journal of Environmental Health, a publication of the National Environmental Health Association, www.neha.org.
Keywords: hydraulic fracturing, gas extraction, frac sand mines, frac sand sites, silica exposure, fracking operations, airborne pollutants, crystalline silica, fine particulate matter